Analyzing the Historical Evolution and Trends of Language Teacher Development: A Thematic Review - Thapa, Deepak (Journal of Musikot Campus, 2025)
Language teacher development (LTD) is an indispensable facet of language teacher professional development. Language teaching is enhanced through the development of language teachers. Teacher development is a crucial part of effective language teaching. This paper critically analyses the historical evolution and trends of language teacher development utilizing the thematic review as a key research method. I reviewed the papers systematically with the help of Google scholar database on teacher development focusing on the evolution and practices in teacher education. I found that the scope of teacher education is not as much focused as of language teaching, though teacher education is one important facet of language teaching and professional growth of a language teacher. Additionally, this research revealed that the study of historical evolution of TD received no or very little attention by the researchers. Despite the rich history and the trends of teacher development, it is not is not well-documented. This present study attempted to fill some of its gaps directing the further researchers to explore more on language teacher development in general and language teacher evolution in particular.